PERANCANGAN TATA LETAK MATERIAL DENGAN METODE CLASS BASED STORAGE - Lokaputra, Riduwan; Ardiansyah, Radya Lutfi; Widodo, Kukuh (Jurnal Sains Ilmu Teknologi Industri, 2023)
PT ABC is a manufacturing company engaged in the cable manufacturing industry. PT ABC has several departments, one of which is the warehouse department. The problem that exists in the warehouse section is that there is wastage in updating the location of the material so that it takes excess time to update the location of the material. This is because there is no definite location of the material placement system. The purpose of this study is to eliminate waste in the process of updating the material location. Problem solving to reduce waste is by structuring the placement of material layout locations and making systems that can be integrated and can be accessed directly in the field. The result of this study is a material layout placement system with class A, B, and C groupings. Class A material has a cumulative displacement frequency of 79.5%. Class B materials have a cumulative displacement frequency of 13.5%. Class C materials have a cumulative displacement frequency of 7%.